Ideal Personal Competency Based on Isen Mulang’s Dayak Philosophy - Riswanto, Dody; Hidayat, Ade (Departemen Psikologi Pendidikan dan Bimbingan FIP Universitas Pendidikan Indonesia, 2019)
The aims of this study was to find the ideal personal values of the counselor based on the isen mulang philosophy of the Dayak tribe. The research method used is qualitative where researchers act as key instruments, data collection techniques are interviews, observation and documentation studies. The results of the study are that the isen mulang philosophy contains four main values, namely the value of struggle, the value of heroism, the value of sacrifice, and the value of spirit never giving up. The four elements of the isen mulang values are implemented by counselors in everyday life to form an ideal personal competence of the counselor.